2023
DOI: 10.1128/jb.00164-23
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DraRS in Clostridioides difficile, a Two-Component Regulatory System That Responds to Lipid II-Interacting Antibiotics

Abstract: Clostridioides difficile is a major cause of hospital-acquired diarrhea and represents an urgent concern due to the prevalence of antibiotic resistance and the rate of recurrent infections. C. difficile encodes ~50 annotated two-component systems (TCSs); however, only a few have been studied. The function of these unstudied TCSs is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…Increased lysozyme resistance was discovered in the draS 605* strain, in which a premature stop codon has excised the catalytic portion of DraS ( 35 ). Deletion of DraR, the cognate RR of DraS, restored wild-type lysozyme susceptibility in the draS 605* strain, suggesting that increased lysozyme resistance was due to an excess of active DraR rather than its absence.…”
Section: Commentarymentioning
confidence: 99%
See 4 more Smart Citations
“…Increased lysozyme resistance was discovered in the draS 605* strain, in which a premature stop codon has excised the catalytic portion of DraS ( 35 ). Deletion of DraR, the cognate RR of DraS, restored wild-type lysozyme susceptibility in the draS 605* strain, suggesting that increased lysozyme resistance was due to an excess of active DraR rather than its absence.…”
Section: Commentarymentioning
confidence: 99%
“…Deletion of DraR, the cognate RR of DraS, restored wild-type lysozyme susceptibility in the draS 605* strain, suggesting that increased lysozyme resistance was due to an excess of active DraR rather than its absence. This indicated that DraS might function mainly as a phosphatase for DraR, such that deletion of DraS catalytic activity could lead to an excess of phosphorylated DraR ( 35 ). The authors confirmed this by mutating the phospho-accepting aspartic acid residue of DraR into a glutamic acid—which, as it is longer than an aspartic acid and still contains a negative charge at the end, is a structural mimic of phosphoaspartate and can serve to constitutively activate an RR.…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations